2018
DOI: 10.1177/0886260518808851
|View full text |Cite
|
Sign up to set email alerts
|

Disciplining in Sri Lankan Schools: A Cross-Sectional Study

Abstract: An integral part of a teacher’s job is to correct misbehavior of students. There is scarcity of information on disciplinary methods used by teachers in schools in Sri Lanka. As a part of a larger research, this study was undertaken to fill this gap. A culturally validated questionnaire was used to assess the various disciplinary methods used by 459 teachers, on 948 students, in six districts in Sri Lanka. National, provincial, special education, and private schools were included in this study. The study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This finding extends prior research on revictimization processes (Widom et al, 2008) by suggesting that the transmission of mass trauma into interpersonal violence against children can occur independently from the effects that such mass traumas have on the psychopathology of the parents. In line with previous studies in post-conflict settings (Attar-Schwartz & Khoury-Kassabri, 2015; Catani 2008a; Catani, Schauer, & Neuner, 2008b; de Zoysa, Senarath, & de Silva, 2018; Khoury-Kassabri & Attar-Schwartz, 2014), we have found a high prevalence rate of guardian and peer violence in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…This finding extends prior research on revictimization processes (Widom et al, 2008) by suggesting that the transmission of mass trauma into interpersonal violence against children can occur independently from the effects that such mass traumas have on the psychopathology of the parents. In line with previous studies in post-conflict settings (Attar-Schwartz & Khoury-Kassabri, 2015; Catani 2008a; Catani, Schauer, & Neuner, 2008b; de Zoysa, Senarath, & de Silva, 2018; Khoury-Kassabri & Attar-Schwartz, 2014), we have found a high prevalence rate of guardian and peer violence in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…The positive influence of parental engagement, as observed in this study, is consistent with the previous studies 26 ; parental understanding reduces the odds of experiences of loneliness, anxiety, and suicidal ideation. A similar study in Sri Lanka has found that a large percentage of children experience psychological and physical violence at home and school, with a lifetime prevalence of 46% corporal punishment by parents and 80.4% during a school term 27 . This probably signifies that many parents in Sri Lanka are involved with children but need better strategies and support to deal with the behavioral problems of the children.…”
Section: Discussionmentioning
confidence: 90%
“…A similar study in Sri Lanka has found that a large percentage of children experience psychological and physical violence at home and school, with a lifetime prevalence of 46% corporal punishment by parents and 80.4% during a school term. 27 This probably signifies that many parents in Sri Lanka are involved with children but need better strategies and support to deal with the behavioral problems of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could have influenced the tolerance of violent and aggressive behavior [ 10 ]. Although corporal punishment in schools is officially banned, it continues to occur at home [ 40 ]. Child maltreatment contributes to a child’s normalization of violence according to studies conducted globally [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%